Melastomataceae no Parque Estadual do Biribiri, Diamantina, Minas Gerais, Brasil: tratamento sistemático e comparação florística - Araújo, Inara Montini (2013)
This study aimed a) to carry out a floristic survey of Melastomataceae species occurring in Biribiri state Park located in the city of Diamantina, Minas Gerais; b) identify endemisms throughout the Espinhaço Range; c) determine the conservation status of Melastomataceae species of State Park Biribiri; d) make a floristic comparison with other areas of this chain. and e) realize a systematic tratament with identification key, morphologic descriptions and data on geographic distribuition of subfamilies Memecyloideae and Melastomatoideae, tribes Melastomeae, Merianieae and MiconieaeA floristic survey was carried out through 2011 to 2012 and all specimens are deposited at Herbarium Uberlandense (HUFU). Melastomataceae are represented in the state park Biribiri by 100 species in 23 genera. Melastomatoideae are represented by 99 species, while Memecyloideae has only Mouriri glazioviana. The tribe with the largest number of species is Microlicieae with 48 species, represented by Microlicia (28 species), Lavoisiera (nine species), Cambessedesia (four species), Trembleya (three species), Rhynchanthera (two species), Chaetostoma and Lithobium (one species each). The tribe Melastomeae, with 25 species, are represented by genera Tibouchina (11 species), Comolia, Pterolepis, Siphanthera (three species each), Marcetia (two species), Acisanthera, Desmoscelis and Macairea (one species each). The tribe Merianieae are represented by Huberia piranii and Merianthera sipollisi. The tribe Miconieae, with 24 species, are represented by genera Miconia (14 species), Leandra (five species), Clidemia (three species), Tococa and Ossaea (one species each). The Melastomataceae flora of the State Park Biribiri is more similar to Serra do Cabral and Serra do Cipó floras both located in Serra do Espinhaço (Minas Gerais). The Melastomataceae flora of the Chapada Diamantina is quite distinct of the Melastomataceae flora of the Serra do Espinhaço , mainly due to the peculiarities and high levels of endemism in each sector. Approximately 30% of the Melastomataceae flora of the Espinhaço is endemic in this region, and the Diamantina Plateau and the Serra do Cipo areas with the highest rate of endemism. At least 47 species of Melastomataceae State Park Biribiri are indicated in any category of threat.